2004
DOI: 10.1128/jvi.78.8.3846-3850.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Alpha/Beta and Gamma Interferons with B, T, and Natural Killer Cells in the Defense against Herpes Simplex Virus Type 1

Abstract: The essential components of the immune system that control primary and chronic infection with herpes simplex virus type 1 (HSV-1) in mice were investigated. Infection within the first few days can be controlled by alpha/beta interferon (IFN-␣/␤) alone without significant contribution of B, T, or NK cells. IFN-␣/␤ and IFN-␥ cooperate in the elimination of virus in the absence of these lymphocytes. In contrast, B, T, or NK cells appear to be required to control persistent infection with HSV-1. These results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 47 publications
1
72
1
Order By: Relevance
“…The lethal dose (LD)50 of untreated, neonatal C57BL/6 mice is 10 3 PFU of HSV-1 [4]. This was increased tenfold to 10 4 PFU of HSV-1 after rIFN-a treatment ( Fig. 1) and as previously shown [4].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The lethal dose (LD)50 of untreated, neonatal C57BL/6 mice is 10 3 PFU of HSV-1 [4]. This was increased tenfold to 10 4 PFU of HSV-1 after rIFN-a treatment ( Fig. 1) and as previously shown [4].…”
Section: Resultssupporting
confidence: 61%
“…It is clear from studies using mice lacking type I IFN receptors that type I IFN plays a central role in the protective immune response [9,10]. IFN-a/b is immediately induced after viral attachment, recognition by Toll-like receptors, or after infection and replication in cells [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These results argue that inhibition of the type I IFN response by the 3C protein may be involved in EV71 pathogenesis. Type I IFN plays a crucial role in different aspects of immunity, including DC maturation, T-cell activation, and inhibition of viral replication (15,22,25,49). Therefore, it is reasonable to predict that when expressed during EV71 infection, the 3C protein may modulate not only innate immunity but also adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Human and murine studies suggest that the innate immune response, specifically the ability to produce elevated levels of type I interferon (IFN) at early time points, provides a threshold of resistance to acute HSV-1 infection (44). Although the precise mechanisms by which type I IFNs function during HSV-1 infection are not fully understood in humans, murine studies have shown IFN-␣/␤ to inhibit the onset of immediateearly gene expression (2,22), limit viral spread into the nervous system (13), and activate host defenses such as NK cells (19).…”
mentioning
confidence: 99%